Influencia de los hábitos y estilos de vida saludables en la progresión de daños articulares de la osteoartrosis. - Núñez Altamirano, Mariela Alexandra (2025)
Osteoarthritis is among the most prevalent conditions affecting older adults, often leading to varying degrees of functional disability and negatively impacting perceived quality of life. This study aimed to conduct a literature review to gather up-to-date information on how healthy habits and lifestyles influence the progression of joint damage in osteoarthritis. To achieve this, a basic, descriptive, cross-sectional, documentary investigation was carried out through a non-systematic review of literature published in the past ten years. The corpus consisted of 79 documents, of which 28 were selected as the study sample. Sources included regional databases (Latindex, LILACS, SciELO, and Redalyc) and high-impact international databases (Scopus, MEDLINE, PubMed, and Web of Science). Boolean operators and standardized health descriptors were employed to optimize the search strategy. The main findings include a comprehensive overview of the epidemiological, pathophysiological, clinical, diagnostic, and therapeutic aspects of the disease; an assessment of the relationship between healthy habits and lifestyle factors and the progression of joint deterioration; and an exploration of the underlying mechanisms involved, including biomechanical, inflammatory, and metabolic pathways. It is concluded that healthy habits and lifestyles play a significant role in modulating the progression of joint damage in older adults with a confirmed diagnosis of osteoarthritis.